The Equity Premium Puzzle in Nepal - Neupane, Biwesh (Banking Journal, 2013)
The study concentrates on one of the most famous puzzles in asset pricing, the equity premium puzzle, which was first identified by Mehra and Prescott (1985). The paper examines the existence and extent of the equity premium puzzle in Nepalese market. The equity premium puzzle refers to the fact that common stocks have offered a very high real risk premium over that of risk-free bills, which leads to unexplainable high risk-aversion of the investors. The study considers the time period of 1995/96 to 2007/08. The result shows that the equity premium exists in Nepal even though the advent of the premium is low compared to other developed countries. This could be a surprising result given the Nepalese context. It was found that the risk aversion of Nepalese investors is greater than 10 (the upeer boundary set by Mehra and Prescott, 1985) which do not fit the conventional financial theories resulting in unexplainable equity premium puzzle. DOI: http://dx.doi.org/10.3126/bj.v3i1.7509 Banking Journal Vol.3(2) 2013 pp.28-42